Understanding Diabetic Polyneuropathy and Longevity: What Can We Learn from the Nematode Caenorhabditis Elegans? - Mendler, M.; Schlotterer, A.; Morcos, M.; Nawroth, P. P. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Pathogenesis of late diabetic complications is influenced by a complex interplay of multiple exogenous and intrinsic factors. The well characterised nematode Caenorhabditis elegans is an ideal model to study causes of diabetic polyneuropathy because of its easily accessible nervous system. A repertoire of methods allows the assessment of both morphological and functional glucotoxic damages as well as reduction of lifespan, thereby helping to examine the influence of different pathways and mechanisms on neurodegeneration. Its insulin signalling system allows to directly visualize effects of insulin on high glucose induced neuronal damage, leading to a better understanding of diabetic polyneuropathy.
Keywords: diabetes mellitus; neuropathy; Caenorhabditis elegans; glucotoxic damage; oxidative stress; insulin